1997
DOI: 10.1002/(sici)1097-0215(1997)10+<22::aid-ijc7>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Diet and lung cancer 20+ years later: More questions than answers?

Abstract: A critical review of epidemiological studies on diet and lung cancer over the last 20+ years has not provided overwhelming evidence that higher consumption of vegetables, fruit, low-fat/low-cholesterol foods or such micronutrients as carotenoids, selenium and vitamins A, C or E is associated with reduced lung cancer risk. Results from case-control studies have been more positive, with about one half showing fruit and vegetables or their associated micronutrients to be associated with reduced risk. However, mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…discrepancy between the observation studies and intervention could be explained by the possibility that the excessive doses of β-carotene given in those intervention studies may be carcinogenic in vivo, and that the cooperative action of carotenoids and other compounds in fruits and vegetables is necessary to inhibit carcinogenesis. 1,[3][4][5][6][7] Recently, flavonoids in vegetables, which scavenge free radicals and are strongly antioxidative, have been added to the list of protective compounds. 24,25) A high intake of green-leafy vegetables, oranges and other fruits was, in our study, associated with a significant dose-dependent reduction in risk of lung cancer among males, and a high intake of the latter two was also associated among male current smokers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…discrepancy between the observation studies and intervention could be explained by the possibility that the excessive doses of β-carotene given in those intervention studies may be carcinogenic in vivo, and that the cooperative action of carotenoids and other compounds in fruits and vegetables is necessary to inhibit carcinogenesis. 1,[3][4][5][6][7] Recently, flavonoids in vegetables, which scavenge free radicals and are strongly antioxidative, have been added to the list of protective compounds. 24,25) A high intake of green-leafy vegetables, oranges and other fruits was, in our study, associated with a significant dose-dependent reduction in risk of lung cancer among males, and a high intake of the latter two was also associated among male current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with numerous previous studies. [1][2][3][4][5][6][7]14) However, significantly low HRs were not observed for the highest intake of carrots and squash, and tomatoes. Exposure misclassification may be larger among males than females because males do not usually cook themselves and cannot exactly evaluate their intake of those vegetables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deficiency can increase the likelihood of a range of diseases and is the main cause of blindness in children; an estimated 250,000–500,000 lose their sight worldwide each year [4]. In adults, some studies have found a link between diets low in beta-carotene and some cancers [5], e.g., a higher intake of green and yellow vegetables associated with a decreased risk of lung cancer [6]. However, other studies have been unable to show this protective effect [7].…”
Section: Introductionmentioning
confidence: 99%